The mechanisms of integration in conditions of asymmetry of innovative development of the EU - Oksana Okhrimenko (CES Working Papers, 2017)
The article concerns to methodological and applied aspects of integration mechanisms functioning in the field of innovation activity of the EU countries. Evolution of models of innovative processes and the detailed forms of integration in their section were investigated. The innovative strategies of EU member states in the context of integration and their effectiveness were analysed. The attention is focused on the transfer of knowledge as the main resource of international cooperation. The advantages of a common innovation environment for participants were considered. The experience of innovative development of the leaders of the countries was highlighted. Requirements for companies planning to innovate or implement innovative projects were disclosed. Preliminary recommendations for eliminating asymmetry in EU innovation development were formulated.
Keywords: 330; integration; innovation activity; transfer of knowledge; innovation policy; project